Changes in Employment in Poland and Abroad Among Rural Population of Opolskie Voivodship in 2008 and 2010 - Jończy, Romuald; Rokita-Poskart, Diana (Regional Barometer. Analyses & Prognoses, 2012)
The existence of considerable gaps in knowledge on employment and international migration, as well as the effects and determinants of the phenomena, became the primary reason for conducting the research on international migration in the Opolskie Voivodship. Apart from the important information about the state of employment, the key issue seemed to be changes in migration that was observed during the recent period in the Opolskie Voievodship. The changes which have occurred due to the macroeconomic situation, such as the economic crisis in Europe and changes in the labor market, determine the profitability of a job abroad. The article presents the results of the research that indicated some positive trends in employment in the country and abroad in the period 2008–2010. Firstly, it shows a significant drop on the scale of emigration in the past two years and a contemporary increase in employment in the country of the Opolskie Voivodships’ inhabitants. On the other hand, the research shows a decrease in the number of people who are economically inactive. Changes in employment were not similar in the various population groups — the most pronounced differences in the change in employment abroad have been associated with the groups of citizenship.